2002
DOI: 10.2527/2002.802421x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary betaine on nutrient utilization and partitioning in the young growing feed-restricted pig2

Abstract: The purpose of this study was to examine the effects of dietary betaine over a range of concentrations (between 0 and 0.5%) on growth and body composition in young feed-restricted pigs. Betaine is associated with decreased lipid deposition and altered protein utilization in finishing pigs, and it has been suggested that the positive effects of betaine on growth and carcass composition may be greater in energy-restricted pigs. Thirty-two barrows (36 kg, n = 8 pigs per group) were restrictively fed one of four c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
5
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 18 publications
(37 reference statements)
3
69
5
3
Order By: Relevance
“…In contrast, other studies in finishing pigs have reported minimal or no effects of betaine on growth, feed intake or body fat (Matthews et al, 1998;Overland et al, 1999). In young, feedrestricted pigs, total body composition analysis indicated that betaine was associated primarily with decreased carcass fat, and an increase in protein deposition, particularly at higher levels of betaine intake (Fernandez-Fıgares et al, 2002).Ḿ uch of the evidence from growth trials, including from our lab (Fernandez-Fıgares et al, 2002),ś uggests that betaine may indeed depress overall fat deposition, and this study focused on betaine's potential stimulatory effects on lipid oxidation as a possible mechanism of action for fat reduction in growing pigs. Information on the role of betaine in altering lipid metabolism in the pig is limited to growth studies.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…In contrast, other studies in finishing pigs have reported minimal or no effects of betaine on growth, feed intake or body fat (Matthews et al, 1998;Overland et al, 1999). In young, feedrestricted pigs, total body composition analysis indicated that betaine was associated primarily with decreased carcass fat, and an increase in protein deposition, particularly at higher levels of betaine intake (Fernandez-Fıgares et al, 2002).Ḿ uch of the evidence from growth trials, including from our lab (Fernandez-Fıgares et al, 2002),ś uggests that betaine may indeed depress overall fat deposition, and this study focused on betaine's potential stimulatory effects on lipid oxidation as a possible mechanism of action for fat reduction in growing pigs. Information on the role of betaine in altering lipid metabolism in the pig is limited to growth studies.…”
Section: Introductionmentioning
confidence: 51%
“…Only females were used in the current growth study, while we used castrated males in our previous growth trial (Fernandez-Fıgares et al, 2002). When male andf emale pigs have been compared directly, conflicting results have been previously obtained with respect to ability of betaine to alter growth and lipid metabolism (Lawrence et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This study was designed to investigate possible mechanisms involved in the increased protein deposition and decreased fat content previously shown in the carcass of pigs fed diets supplemented with betaine and CLA (Ostrowska et al, 1999 andFerná ndez-Fígares et al, 2002 and2008;Mitchell et al, 2005). Serum metabolites and hormones that may indicate a modification in protein or energy metabolism were investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical analyses of the basal diet were carried out according to the methods of AOAC (1990), as described by Ferná ndez-Fígares et al (2008). Hormones were measured using commercially available radio-immuno assay (RIA) or immuno-radiometric assay (IRMA) kits following the directions of the manufacturer, and the assays were validated for use in porcine serum in our laboratory (Ferná ndez-Fígares et al, 2007).…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation